The Effect of STEM Learning Method on Students’ Mathematical Concepts Understanding in Social Arithmetics Topic - Virla Arlavinda; Nurul Anriani (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
Mathematical concepts understanding is the main foundation for mastery of more complex material so that appropriate learning methods are needed to improve students' understanding of mathematical concepts. This study aims to determine the effect of the Science, Technology, Engineering, and Mathematics (STEM) learning method on the students' mathematical concepts understanding in social arithmetic topic. The research method used in this study was a quasi-experimental design with a nonequivalent pretest-posttest control group design. This research was conducted at a junior high school in Serang, Banten, using a probability sampling technique. The instrument used is a test of the mathematical concepts understanding. The test results of the mathematical concepts understanding were analyzed using the t-test and N-Gain to determine the increase in students' mathematical concepts understanding. The results showed that the STEM learning method had a significant influence on increasing students' mathematical concepts understanding in social arithmetic topic. However, the use of the STEM learning method to improve students' mathematical abilities in general in various mathematical materials still requires further research.